"Almost everything is unusual and indescribably eccentric": Church opposition to The Salvation Army during its first years in Norway. (3rd July 2017) - Elstad, Hallgeir
Abstract : The Salvation Army was established in Norway towards the end of the nineteenth century. It attracted considerable attention, first and foremost because of its unorthodox methods of evangelization. The Army met opposition from the official church. In this article, this opposition will be examined. What was it about The Salvation Army that caused attacks from the Church, and what arguments were used in this criticism?